The Relationships between Commodity Prices, Firm Performance and Stock Valuation: An Empirical Evidence from Malaysia and Singapore - Le, Quang Thanh (2013)
The study estimates the commodity prices and firm performance risk exposures of the Malaysian and Singaporean plantation and other related commodities’ sectors, using the Ohlson (1995)’s, Easton and Harris (1991)’s and other related asset prices together with return models augmented with accounting factors. Results show that the firm performance factors affect significantly and strongly stock valuation. However, the commodity prices affect determinants of firm performance and stock valuation weakly. The study also finds that both the commodity prices and firm performance together affect stock prices more significantly than the stock returns do. However, both of the constructed models which show the impacts of commodity prices and firm performance on stock valuation have better explanation than Ohlson (1995)’s and Easton and Harris (1991)’s models. This study proves that the relationships among commodity prices, firm performance and stock valuation of plantation and agriculture sectors are more considerable than other sectors’ over time.